Plasma lipid profiles and homocysteine levels in anti-N-methyl-D-aspartate receptor encephalitis - Wang, Zhi-hao; Qiao, Shan; Wang, Lei; Wang, Kemo; Zhang, Ranran; Jin, Yang; Wu, Huai-kuan; Liu, Xuewu (Frontiers in Neurology, 2023)
Abstract Introduction We aimed to investigate whether lipid profiles and homocysteine levels in patients with anti-NMDAR encephalitis are related to clinical presentation and prognosis, which may contribute to further research on the pathogenesis and treatment of this disease. Methods This study included a total of 43 patients with anti-NMDAR encephalitis and 43 sex-age-matched healthy controls.Baseline demography, clinical data, patient outcomes, and ancillary examination results were recorded.Patients were followed up every 2-3 months during the first year. The mRS score was used to evaluate the therapeutic effect and clinical outcome. Results Among the 43 patients included in this study, 55.81% were male, the mean age of onset was 27 years old , and the median mRS Score on admission was 3.0. ApoA-1 was significantly lower in patients with anti-NMDAR encephalitis compared with healthy controls (p < 0.01). Compared with CTL, Hcy (p < 0.01), ApoB (p < 0.01), Lpa (p < 0.05) and ApoB/ApoA-1(p < 0.01) were significantly increased in patients with anti-NMDAR encephalitis. According to mRS Scores 6 months after discharge, 72.09% of patients had a good prognosis and 27.91% had a poor prognosis. In the good prognosis group, age (p= 0.031), lipoprotein a (p=0.023), mRS Score on admission ( p=0.019), and ApoA-1 was significantly higher than poor prognosis group (p=0.027). Conclusion This study suggests the possibility that serum lipid profile and homocysteine play an important role in the pathogenesis of anti-NmdAR encephalitis, providing support for lipid-lowering treatment of anti-NMDAR encephalitis patients. Key words:Anti-N-methyl-D-aspartate receptor encephalitis; Lipid profile; Homocysteine；ApoB/ApoA-1; prognosis.